Repressed OsMESL expression triggers reactive oxygen species‐mediated broad‐spectrum disease resistance in rice. Issue 8 (6th April 2021) - Hu, Bin; Zhou, Yong; Zhou, Zaihui; Sun, Bo; Zhou, Fei; Yin, Changxi; Ma, Weihua; Chen, Hao; Lin, Yongjun
Abstract: A few reports have indicated that a single gene confers resistance to bacterial blight, sheath blight and rice blast. In this study, we identified a novel disease resistance mutant gene, methyl esterase‐like ( osmesl ) in rice. Mutant rice with T‐DNA insertion displayed significant resistance to bacterial blight caused by Xanthomonas oryzae pv. oryzae ( Xoo ), sheath blight caused by Rhizoctonia solani and rice blast caused by Magnaporthe oryzae . Additionally, CRISPR‐Cas9 knockout mutants and RNAi lines displayed resistance to these pathogens. Complementary T‐DNA mutants demonstrated a phenotype similar to the wild type (WT), thereby indicating that osmesl confers resistance to pathogens. Protein interaction experiments revealed that Os MESL affects reactive oxygen species (ROS) accumulation by interacting with thioredoxin Os Trxm in rice. Moreover, qRT‐PCR results showed significantly reduced mRNA levels of multiple ROS scavenging‐related genes in osmesl mutants. Nitroblue tetrazolium staining showed that the pathogens cause ROS accumulation, and quantitative detection revealed significantly increased levels of H2 O2 in the leaves of osmesl mutants and RNAi lines after infection. The abundance of JA, a hormone associated with disease resistance, was significantly more in osmesl mutants than in WT plants. Overall, these results suggested that osmesl enhances disease resistance to Xoo, R. solani and M . oryzae by modulating the ROS balance.